Effect and mechanism of eugenol on storage quality of fresh-peeled Chinese water chestnuts - Chen, Zhe; Xu, Yuhan; Lu, Yang; Miao, Zeyu; Yi, Yang; Wang, Limei; Hou, Wenfu; Ai, Youwei; Wang, Hongxun; Min, Ting (Frontiers in Plant Science, 2022)
The study aimed to investigate the effect and mechanism of eugenol treatment on fresh-peeled Chinese water chestnuts (CWCs). The results found that eugenol treatment maintained the appearance of fresh-peeled CWCs, accompanied by higher L* value, total solids and O2 contents, as well as lower browning degree, weight loss rate, CO2 content, a* and b* values. In addition, eugenol treatment significantly reduced the activities of peroxidase, phenylalanine ammonia-lyase, and polyphenol oxidase, as well as the total content of soluble quinone in fresh-peeled CWCs. Meanwhile, fresh-peeled CWCs treated with eugenol showed markedly lower content of total flavonoids, which may be related to yellowing. Furthermore, eugenol treatment suppressed the rates of O2·- and OH·- production as well as the contents of H2O2 and malondialdehyde in fresh-peeled CWCs. During the storage, eugenol treatment not only increased the activities of catalase, superoxide dismutase, ascorbate peroxidase and glutathione reductase as well as the DPPH free radical scavenging rate, but also increased the total phenolics, ascorbic acid and glutathione contents. In summary, eugenol treatment delayed the surface discoloration of fresh-peeled CWCs by improving the antioxidant capacity, inhibiting the phenolic compound metabolism and scavenging ROS, thus effectively maintaining the quality of fresh-peeled CWCs while extending their shelf life.